Using Inhomogeneous Planar Layers as Impedance Matchers between Two Different Mediums. (18th February 2008) - Khalaj-Amirhosseini, Mohammad
Abstract : A method is proposed to synthesize optimally inhomogeneous planar layers (IPLs) as impedance matchers between two mediums. First, the electric permittivity function of the IPL is expanded in a truncated Fourier series. Then, the optimum values of the coefficients of the series are obtained through an optimization approach. The usefulness of the proposed method is verified using some examples.